Antenna theory and applications - Visser, Hubregt J. (Chichester, West Sussex, U.K. : John Wiley & Sons, 2012)
This comprehensive text on antenna theory explains the origin of radiation and discusses antenna parameters in-depthThis book offers an in-depth coverage of fundamental antenna theory, and shows how to apply this in practice. The author discusses electromagnetic radiation and antenna characteristics such as impedance, radiation pattern, polarization, gain and efficiency. In addition, the book provides readers with the necessary tools for analyzing complex antennas and for designing new ones. Furthermore, a refresher chapter on vector algebra, including gradient, divergence and curl operation is included. Throughout the book ample examples of employing the derived theory are given and all chapters are concluded with problems, giving the reader the opportunity to test his/her acquired knowledge.
Introduction -- Antenna system-level performance parameters -- Vector analysis -- Radiated fields -- Dipose antennas -- Loop antennas -- Aperture antennas.
Includes bibliographical references and index.
Print version record.
Keywords: Antennas (Electronics); Electrical engineering; Engineering; Antennas (Electronics); TECHNOLOGY & ENGINEERING -- Telecommunications; Antennas (Electronics); Electrical engineering; Engineering; Antennas (Electronics); Electronic books; Electronic books